Doped ceramics of indium oxides for negative permittivity materials in MHz-kHz frequency regions. (20th January 2021) - Fan, Guohua; Wang, Zhongyang; Sun, Kai; Liu, Yao; Fan, Runhua
Highlights: Tin doped indium oxides can be epsilon-negative materials at MHz-kHz frequencies. Negative permittivity was affected by doping dynamics in different sintering atmosphere. Temperature-dependent negative permittivity and ac conductivity were investigated. Carriers concentration was determined to influence the epsilon-negative properties. Negative permittivity was attributed to and influenced by free carriers' collective oscillations. Abstract: Negative permittivity has been widely studied in various metamaterials and percolating composites, of which the anomalous dielectric behavior was attributed to critical structural properties of building blocks. Herein, mono-phase ceramics of indium tin oxides (ITO) were sintered for epsilon-negative materials in MHz-kHz frequency regions. Electrical conductivity and complex permittivity were analyzed with Drude-Lorentz oscillator model. Carriers' characters were measured based on Hall effect and the magnitude and frequency dispersion of negative permittivity were mainly determined by carrier concentration. Temperature-dependent dielectric properties further proved the epsilon-negative behaviors were closely associated with free carriers' collective responses. It's found that negative permittivity of ITO ceramics was mainly caused by plasma oscillations of free carriers, while the dielectric loss was mainly attributed to conduction loss. Negative permittivity realized here was related to materials intrinsic nature and this work preliminarily determined the mechanism of negative permittivity in doped ceramics from the perspective of carriers.